The Effect of Combination of Fermentation and Commercial Feed on The Immunity of Super Native Chicken - D. Desniatin; H. Husnaeni; J. Junaedi (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
This study aims to determine the effect of providing a combination of commercial fermented feed on the resistance of super native chicken. The study was conducted from October to December 2019 in the Popalia village Tanggetada Kolaka district. The material used is 60 super native chicken DOC. The study was arranged in a completely randomized design 4 treatments and 3 replication P1 (40% fermented feed + 60% commercial feed), P2 (50% fermented feed + 50% commercial feed), P3 (60% fermented feed + 40% commercial feed), P4 (70% ferment and feed + 30% commercial feed). The parameter observed included Fabricius, thymus, and spleen exchanges. The provision of fermented and commercial feed in non-significant feed has a significant percentage of the body weight of primary lymphoid organs (Fabricius thymus exchanges) and the percentage of secondary lymphoid organs (spleen)